Efecto de tres fuentes de materia organica (vacaza,gallinaza y cuyaza),enriquecidos con microorganismos beneficos(EM) en culltivo de lechuga (lactuca sativa .L) Lamas - Oliveira Rios, Cristhiam Waldemar (2010)
This essay titled "Effects of composted organic matter from three sources (cow, chicken and whose) enriched with effective microorganisms in the cultivation of lettuce ( Lactuca sativa L.) in the district of Lamas," has as main objective to evaluate the productivity lettuce crop by applying organic fertilizer enriched with effective microorganisms, which would promote the use of environmentally and economically viable alternatives for inclusion in agricultural production. We studied three sources of organic manure (cattle, chicken and whose) enriched with effective microorganisms and a witness, in the cultivation of lettuce. The design that was used was a DBCA with four treatments and five repetitions and for comparison and analysis test was conducted according to Duncan means comparison, with a significance of 5%. Field measurements were evaluated, the arrest rate, leaf area, healthy leaves and total crop yield per square meter. The results show that in T1 (which + 666,66 ml of E.M.) obtained a higher yield with 2.92 kg/m2 compared to treatment T3 (manure + 666,66 ml of E.M.), T2 (cows + 666,66 ml of E.M.) and T0 (control), which were 2.51, 2.48 and 2.19 kg/m 2 r espectively. Which show a highly significant difference between treatments according to the comparative analysis of DUNCAN ( α = 0.05).